Manganese-catalyzed C–C and C–N bond formation with alcohols via borrowing hydrogen or hydrogen auto-transfer - Ansari, Mohd Farhan; Maurya, Atul Kumar; Kumar, Abhishek; Elangovan, Saravanakumar (Beilstein Journal of Organic Chemistry, 2024)
Transition-metal-mediated “borrowing hydrogen" also known as hydrogen auto-transfer reactions allow the sustainable construction of C–C and C–N bonds using alcohols as hydrogen donors. In recent years, manganese complexes have been explored as efficient catalysts in these reactions. This review highlights the significant progress made in manganese-catalyzed C–C and C–N bond-formation reactions via hydrogen auto-transfer, emphasizing the importance of this methodology and manganese catalysts in sustainable synthesis strategies.
Keywords: alcohols; alkylation; amines; borrowing hydrogen; hydrogen auto-transfer; manganese